Internalization of Character Education in Islamic Perspective and Its Implementation in Daily Life - Kamaluddin, R. Tamtam; Sa’diyah, Maemunah; Ibdalsyah, Ibdalsyah; Bahruddin, E (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study discusses the internalization of character education from an Islamic perspective and its implementation in daily life. Character education according to Islam aims to form individuals who have noble personalities (moral character) by instilling values ​​such as honesty, trustworthiness, compassion, responsibility, and mutual respect. The process of internalizing character education is carried out through various methods, including direct teaching, role models, practicing the teachings of the Quran and Hadith, and habituation in the family, school, and community environments. The implementation of Islamic character values ​​in daily life not only leads to the formation of superior individuals but also to the formation of a harmonious and prosperous society. With a systematic approach, Islamic perspective character education can be the main foundation in building a generation with noble morals and high social awareness. The results of this study indicate that the integration of Islamic values ​​into daily activities has a significant impact on forming good individual characters, which are in line with the goals of Islamic education, namely achieving happiness in the world and the hereafter.